Peningkatan Semangat Berwirausaha Pada Mahasiswa Melalui Model Project Based Learning - Nafiati, Dewi Amaliah (Universitas Muhammadiyah Gresik, 2019)
ABSTRACTThis research aims to identify whether using the project based learning model in entrepreneurship practice courses take effect the entrepreneurial spirit of S1 fourth semester economics education students in 2017/2018. Quantitative research approach, the population in this study were all fourth semester students of Economic Education, FKIP Pancasakti Tegal University as many as 28 students. The sampling technique is used quota sampling technique. Data collection methods used are questionnaires. The data analysis technique for this research used a simple linear regression test and t test.The calculation results obtained F value = 0.895 with significance level of 0.035 <0.05 and the big influence caused 0,536. The linear regression equation Y = 29,010 + 0,208 X, the meaning every 1 point increase in variable of The Project Based Learning models in the Entrepreneurship Practice Course will influence the variable Entrepreneurship in Economic Education Students in Fourth Semester of 0.208. Based on these calculations then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This means that there is a significant influence on the Project Based Learning model in the Entrepreneurship Practice Course towards Entrepreneurial spirit in the fourth Semester Economic Education Students